Respuesta :

Answer:

[tex]u=\frac{9}{t}-\frac{1}{2} a t[/tex]

Step-by-step explanation:

Step 1: Given equation: [tex]9=\frac{1}{2} a t^{2}+u t[/tex]

To get u, by subtraction equality property subtract both sides of the equation by  [tex]\frac{1}{2} a t^{2}[/tex].

[tex]\Rightarrow 9-\frac{1}{2} a t^{2}=\frac{1}{2} a t^{2}+u t-\frac{1}{2} a t^{2}[/tex]  

[tex]\Rightarrow 9-\frac{1}{2} a t^{2}=u t[/tex]  

Step 2: By division equality property, divide both sides of the equation by t.

[tex]\Rightarrow \frac{9-\frac{1}{2} a t^{2}}{t}=\frac{u t}{t}[/tex]

[tex]$\Rightarrow \frac{9}{t}-\frac{1}{2} a t=u$[/tex]  

Therefore, [tex]$u=\frac{9}{t}-\frac{1}{2} a t$[/tex].

So, in Emily’s physics class, she got [tex]$u=\frac{9}{t}-\frac{1}{2} a t$[/tex].